DYREETIK - Sandøe, Peter (Tidsskriftet Antropologi, 1996)
Peter Sandøe: The Ethics of Animals The paper is about man’s duties to animals. It consists of two main parts. The first part is a critical discussion of the view, influential in western philosophy, that we have no moral obligations to animals. Particularly two lines of argument are discussed. This first is the argument inspired by Aristotle and Thomas Aquinas, that animals have no moral standing because they lack rationality. The second is the argument, inspired by René Descartes, that we owe no moral consideration to animals because they, allegedly, lack consciousness. The author concludes that both arguments fail, and that we ought to accept a moral obligation to look after the interests of animals. The second part is a discussion of modem animal production. Broiler chickens, battery hens, veal calves, tethered and stalled sows and other farm animals will often suffer and will all lack the ability to do things which could contribute to their “positive welfare”. The interests of these animals are set aside so that the production can be as efficient as possible. Consequently consumers are able to buy very cheap meat and other animal products. However, in the rich part of the world there is no reason to think that these cheap products are vital to human interests. There is a discussion of methods for measuring the welfare of farm animals. Finally, there is a presentation of intitiatives to improve the welfare of farm animals in Denmark and the EU.